Identificação de bolhas em ações e o desempenho financeiro: uma análise para as instituições mais relevantes do índice IFNC - Veiga, Matheus Borgatto Cerino da (Universidade Federal de São Carlos, 2026)
Considering the importance of financial sector firms to the country’s economy, as facilitators of financial flows and providers of purchasing power, the objective of the present study is to quantify the existence of bubbles in the share prices of the common shares of the companies with the greatest weight in the IFNC index, namely Banco do Brasil S.A. (BBAS3), Banco Bradesco S.A. (BBDC3), IRB Brasil Resseguros S.A. (IRBR3), Banco Itaú S.A. (ITUB3), and Porto Seguros S.A. (PSSA3), and to relate the dated bubbles to the disclosure of the financial results of the firms analyzed. In doing so, the study seeks to discuss whether the bubbles in the share prices of these companies may be associated with economic and or financial events or whether they are temporally linked to the firms’ results. The data used consist of the closing prices of the shares of the companies mentioned above, covering the period from 31 July 2017 to 27 June 2025. Bubble identification followed the PSY procedure, based on the Generalized Supremum Augmented Dickey Fuller (GSADF) test, complemented by a Wild Bootstrap procedure to ensure more robust inference and reduce the risk of spurious detections. The study integrates bubble dating with traditional economic and financial performance indicators, namely ROA and ROE. The results show that the identification of episodes of explosive behavior is not always accompanied by a clear deterioration or improvement in fundamentals. At certain moments, the identified bubbles appear to be supported by actual changes in profitability, whereas at others they reflect expectations and narratives that go beyond what is observed in the companies’ financial statements.
Identifying bubbles in stocks and financial performance: an analysis for the most relevant institutions of the IFNC
Keywords: Bolhas; Roe; Bancos; IFNC; Roa; Bubbles; Banks; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; 4. Educação de Qualidade